If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(t + 2) = 4 Reorder the terms: -4(2 + t) = 4 (2 * -4 + t * -4) = 4 (-8 + -4t) = 4 Solving -8 + -4t = 4 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -4t = 4 + 8 Combine like terms: -8 + 8 = 0 0 + -4t = 4 + 8 -4t = 4 + 8 Combine like terms: 4 + 8 = 12 -4t = 12 Divide each side by '-4'. t = -3 Simplifying t = -3
| 50k+180=40k+120 | | x+34+x+47=69 | | -3(x+4)-6(x-4)=12 | | 24-12x=20 | | 34.95+4x=200 | | 2n^2(5n+3)= | | bw+y=2y | | 5.8(1-6.8p)=246.384 | | (6x^2y^-1/8x^-3y)^2 | | -4(-2)+3(4+2v)= | | -4x+12=-4x+4 | | 4sin^2(x)=1 | | 3X+4X+8X+6X+5X=360 | | (4x-1)+(2x-1)=2x | | -5+6r=4r+1r | | 2/2y=2/2(y-2) | | 8x+9+6x-3=34 | | 5x+6=(4x+7) | | 5p-4p^2=0 | | -6(k+7)=-90 | | x+6=(3-x) | | -101=r/3 | | 16y^2z+20y^3z^6= | | 3X+4x+8x+6+5X=360 | | -11-6v=-7v-5 | | (y+z)*12= | | -5+y=-5 | | -13-7x=6-9(n+3) | | X+17=6x+1 | | 6x+6+4+4x=3x*3+1x+1 | | 20uv-15u= | | 8-1/5x=13 |